NREM and REM sleep parasomnias: clinical cases and literature review - Teišerskytė , K.; Čelpačenko , I.; Pajėdienė , E. (Neurologijos seminarai, 2021)
Parasomnias are a group of sleep disorders that manifest as abnormal behaviour or movements while falling asleep, during sleep, or before awakening. According to the International Classification of Sleep Disorders (ICSD-3), parasomnias are subdivided into non-rapid eye movement (NREM) and rapid eye movement (REM) parasomnias. Main types of NREM parasomnias include disorders of arousal which consist of confusional arousals, sleepwalking, and sleep terrors, as well as sleep-related abnormal sexual behaviour and sleep-related eating disorder (SRED). The prevalence of NREM parasomnias in children and adolescents is higher than in adults. NREM parasomnias are often benign, self-limited, or resolved with non-pharmacological treatment, while REM sleep behaviour disorder (example of REM parasomnias) is much more likely to occur in adult age and is associated with neurodegenerative diseases. There are 3 types of parasomnias associated with REM sleep: REM sleep behaviour disorder (RBD), isolated sleep paralysis, and nightmare disorder. Parasomnias can significantly disrupt the sleep quality of patients and their bed partners, day-time wakefulness, and can be hazardous. Detailed sleep history and clinical examination are of essential significance in differential diagnosis between sleep disorders, nocturnal epilepsy, and psychiatric disorders. Non-pharmacological interventions such as sleep hygiene and safe sleeping environment play an important role in management of parasomnias.
Keywords: sleep disorders; NREM parasomnias; REM parasomnias; polysomnography